EVENT-DRIVEN ARCHITECTURE FOR REAL-TIME NOTIFICATION SYSTEMS IN STUDENT ENVIRONMENTS: A PERFORMANCE AND SCALABILITY STUDY USING THE WHATSAPP API - Poetri Lestari Lokapitasari Belluano; Abd. Majid; Muhammad Nur Fuad; Muhammad Rifky Saputra Scania (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2026)
Event notification systems play a crucial role in supporting academic and student organizational activities. However, many institutions still rely on monolithic architectures with synchronous processing that are unable to handle spikes in communication loads, resulting in high latency and reduced delivery reliability. This study proposes a notification system based on Event-Driven Architecture (EDA) integrated with a microservices environment to improve the efficiency, scalability, and reliability of information dissemination, particularly through the WhatsApp Business API as the primary communication channel. The proposed system leverages asynchronous event processing, distributed message brokers, and isolated gateway services to enable parallel message delivery while addressing external service constraints such as rate limiting. The system is evaluated within a single controlled experimental setup using 1,011 notification messages under consistent workload conditions. For comparison purposes, a simulated synchronous baseline is used to represent the characteristics of traditional sequential processing systems. The results show that the EDA-based system achieved a 100% delivery success rate with an average latency of 3,222 ms and a stable throughput of 17 messages per second, while the simulated baseline exhibits limitations in maintaining performance under the same conditions. These findings indicate that the proposed architecture improves system performance within the evaluated experimental context and demonstrates strong potential for scalable real-time communication in controlled deployment environments.